Spontaneous Remission of Sick Sinus Syndrome in a Fetus with Pulmonary Stenosis Regurgitation - Kajiwara, Kazuhiro; Ishikawa, Satoru; Mori, Takuma; Samura, Osamu; Okamoto, Aikou (American Journal of Perinatology Reports, 2019)
Objective Here, we report a case of fetal sick sinus syndrome (SSS) caused by pulmonary stenosis regurgitation (PSR) that spontaneously resolved during pregnancy.Case Report A 29-year-old woman was referred to our hospital at 21 weeks of gestation for persistent fetal bradycardia. Fetal echocardiography revealed PSR and ventricular septal defect (VSD). The ventricular rate was 60 to 70 beats/minute with 1:1 atrioventricular conduction. Thus, congenital SSS owing to PSR was suspected. During pregnancy, fetal SSS spontaneously resolved at 28 weeks of gestation despite persistent PSR. The ventricular rate was increased to approximately 120 beats/minute with regular rhythm. A 2,390-g male neonate was delivered via Caesarean section at 38 weeks of gestation. Consequently, detailed echocardiography revealed PSR and VSD without SSS.Conclusion Although fetal PSR can cause fetal SSS owing to immaturity at an earlier gestational age, SSS might be spontaneously resolved by fetal heart development as pregnancy progresses.
Keywords: pulmonary stenosis regurgitation; sick sinus syndrome; fetal echocardiography; fetal bradyarrhythmia; congenital heart disease